A caution for conservation stocking as an approach for recovering Atlantic eels. Issue 4 (5th September 2014) - Stacey, Joshua A.; Pratt, Thomas C.; Verreault, Guy; Fox, Michael G.
Abstract Worldwide concerns about declining eel stocks have resulted in the increased use of conservation stocking (i.e. the translocation of early eel life‐stages from areas of high recruitment to areas experiencing recruitment declines) as a recovery tool. North Atlantic eels have complicated and incompletely understood life‐history strategies with major differences in life‐history parameters across the species' broad distributions, and these differences may be important for migrating and spawning successfully. Sex ratio, growth rate and size and age at maturation of American eels (Anguilla rostrata) stocked into the St. Lawrence River basin from donor areas over 2000 km away with differing life‐history characteristics were compared with those of naturally recruited eels to assess the effectiveness of a potential stocking programme in maintaining a sub‐population with unique life‐history characteristics (largest from across the species range, and exclusively female). Stocked eels exhibited faster annual growth, had a different sex ratio, and matured and outmigrated at smaller sizes and ages than naturally recruited eels. Conservation stocking should be applied with caution, as stocked eels appear to be following life‐history patterns comparable with conspecifics in the geographic range of the donor streams where they were collected. These findings cast doubt on the generally accepted hypothesis that the mechanisms driving eel life‐history variation are environmentally induced, and suggest that more care should be taken in assessing and matching the life‐history characteristics of donor and recipient sub‐populations if conservation stocking is expected to be an important recovery option for eel restoration. © 2014 Her Majesty the Queen in Right of Canada. Aquatic Conservation: Marine and Freshwater Ecosystems © 2014 John Wiley & Sons, Ltd.